CANTAR PARA QUÊ? A música gospel no processo de midiatização: o caso do programa Esquenta! - OLIVEIRA, JENIFER ROSA DE (2016)
This research aims at analyzing the aspects under which the interaction between media and religion takes place, as well as the intricacies and continuities evoked by bringing the sacred and the profane together. For that purpose, the appearance of evangelical Christian artists on the TV Show Esquenta!, which is broadcasted every Sunday afternoon by the TV Channel Globo, has been elected as the subject matter of this study. The concepts on the gospel culture, on mediatization - particularly that of the media driven bios, and the discussion on secularization, as proposed by Habermas, have been chosen as this study's theoretical framework. The methodology provides two stages. The first one consists on investigating the content of five editions of Esquenta!, broadcasted between 2013 and 2014, on which evangelical Christian artists appeared. At that point, this stage's goal was the realization of the role that the Gospel Music plays within the Show's approach. The second stage consists in forming two discussion groups: one group of evangelical Christians and one group of non-evangelical people. This stage's goal was the understanding on how religious contents meanings, outside of their original context, can be re-depicted by the audience. The study results in the perception that the gospel artists performances on Esquenta! provides for new ways to interpret concepts around the Gospel culture, which amplify it and legitimate the media as a locus for religious experience. Furthermore, it illustrates the Habermasian perspective as it reflects the dual affectation between the religious universe and the secular life, emerging from intercrossing media and religion